Government's Intervention on failure of small and medium enterprises in South Africa - Theletsane, Joyce Masentle (University of the Free State, 2020)
Small and Medium Enterprises (SMEs) make a tremendous contribution to worldwide economies. In South Africa, they are considered the lifeblood of the economy as they are expected to address the high unemployment and poverty rates which the country is experiencing. However, it has come to light that SMEs do not grow in South Africa. It is thus critical to study factors which cause failure within the SME sector. This study investigates the factors that cause SME failure, which are divided into two environments, namely the micro- and the macro-environment. The study further investigates the effectiveness of the three strategies that entail the South African small business policy and effectiveness of institutions created by government to assist and support SMEs, i.e. Small Enterprise Development Agency, National Youth Development Agency and Small Enterprise Finance Agency.
Dissertation (MGT (Governance and Political Transformation))--University of the Free State, 2020
Keywords: SMEs; LED; entrepreneurship; entrepreneurs; business failure; ISEDS; ISPSES; poverty; GDP; inequality